Prevalence of Mental Illness among Homeless People in Hong Kong - Yim, Larina Chi-Lap (PLoS One, 2015)
METHOLODOGY: This study examined the prevalence and correlates of mental illness in homeless people in Hong Kong and explored the barriers preventing their access to health care. Ninety-seven Cantonese-speaking Chinese who were homeless during the study period were selected at random from the records of the three organisations serving the homeless population. The response rate was 69%. Seventeen subjects could not give valid consent due to their poor mental state, so their responses were excluded from the data analysis. A psychiatrist administered the Structured Clinical Interview for DSM-IV Axis-I disorders (SCID-I) and the Mini -Mental State Examination. Consensus diagnoses for subjects who could not complete the SCID-I were established by three independent psychiatrists. FINDINGS: The point prevalence of mental illness was 56%. Seventy-one percent of the subjects had a lifetime history of mental illness, 30% had a mood disorder, 25% had an alcohol use disorder, 25% had a substance use disorder, 10% had a psychotic disorder, 10% had an anxiety disorder and 6% had dementia. Forty-one percent of the subjects with mental illness had undergone a previous psychiatric assessment. Only 13% of the subjects with mental illness were receiving psychiatric care at the time of interview. The prevalence of psychotic disorders, dementia and the rate of under treatment are hugely underestimated, as a significant proportion (18%) of the subjects initially selected were too ill to give consent to join the study. CONCLUSION: The low treatment rate and the presence of this severely ill and unreached group of homeless people reflect the fact that the current mode of service delivery is failing to support the most severely ill homeless individuals.